2013
DOI: 10.1155/2013/593087
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Colonization of Arbuscular Mycorrhiza Fungi in the Roots of Camellia sinensis (Tea) in Different Tea Gardens of India

Abstract: Microscopic study of sterilized and stained root segments showed presence of four species namely Glomus fasciculatum, G. mosseae, Gigaspora margarita, and Acaulospora scrobiculata belonging to three genera of mycorrhizal fungi. Maximum AM colonization was observed during April-September and minimum was observed for December-January months of the year. Comparative study of AM fungi colonization at four sites during rainy season showed maximum colonization (100%) at Archadia site having soil with high organic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Some studies have shown that mycorrhizal fungi spore germination and hyphae colonization are almost completely inhibited at 10 °C (Gpey 1991;Wang et al 2002;Sharma et al 2013), although the growth of some fungal species may be severely inhibited, but not completely ceased at such low temperatures, for example at 10 °C for Glomusintraradices and at 5 °C for Glomus caledonium (Table 1) (Wang et al 2002;Sharma et al 2013). AMF capable of growing in cold soils may show contradictory results from beneficial to parasitic relationships (Charest et al 1993;Sharma et al 2013). This could be due to inability of AMF to uptake and transfer nutrients to the host plant, while consuming plant carbon reservoir (Sharma et al 2013).…”
Section: Plant-arbuscular Mycorrhizal Fungi Symbiosis Under Low Tempementioning
confidence: 99%
See 4 more Smart Citations
“…Some studies have shown that mycorrhizal fungi spore germination and hyphae colonization are almost completely inhibited at 10 °C (Gpey 1991;Wang et al 2002;Sharma et al 2013), although the growth of some fungal species may be severely inhibited, but not completely ceased at such low temperatures, for example at 10 °C for Glomusintraradices and at 5 °C for Glomus caledonium (Table 1) (Wang et al 2002;Sharma et al 2013). AMF capable of growing in cold soils may show contradictory results from beneficial to parasitic relationships (Charest et al 1993;Sharma et al 2013). This could be due to inability of AMF to uptake and transfer nutrients to the host plant, while consuming plant carbon reservoir (Sharma et al 2013).…”
Section: Plant-arbuscular Mycorrhizal Fungi Symbiosis Under Low Tempementioning
confidence: 99%
“…AMF capable of growing in cold soils may show contradictory results from beneficial to parasitic relationships (Charest et al 1993;Sharma et al 2013). This could be due to inability of AMF to uptake and transfer nutrients to the host plant, while consuming plant carbon reservoir (Sharma et al 2013). The optimum ambient temperature for developing many AMF would be between 20 to 30 °C with upper and lower activity thresholds of 34 and 16 °C , respectively, for most strains (Wang et al 2002).…”
Section: Plant-arbuscular Mycorrhizal Fungi Symbiosis Under Low Tempementioning
confidence: 99%
See 3 more Smart Citations